Fatal caffeine intoxication in a dog - Hensel, Martha; Pashmakova, Medora; Porter, Brian F. (Brazilian Journal of Veterinary Pathology, 2017)
An 8-month-old male Yorkshire terrier was presented for ingestion of 800 mg of an over-the-counter caffeine supplement. Clinical signs included extreme tachycardia, facial fasciculation, coma/stupor and flailing. Due to the lack of response to medical therapies, humane euthanasia was elected. Microscopically, necrotic neurons were scattered throughout the hippocampus, olfactory cortex, pyriform lobe, amygdala, and basal nuclei, with relative sparing of the caudate nuclei. In addition, mild skeletal myocyte necrosis and mural necrosis of cardiac arterioles in the left and right ventricles were noted. This is the first report of the microscopic lesions associated with caffeine intoxication in a dog.